The Relationship Between Teenage Pregnancy and Future Maternal Mental Health - Etelvina Jose S. Tilman; Eugenia Carvalho de Araujo; Natalia Pereira; Artur N. Cortereal Araujo; Jose Dionisiio Ximenes (PT. Banjarese Pacific Indonesia, 2024)
This study investigates the relationship between teenage pregnancy and future maternal mental health by using qualitative methods and relying on literature review as the main data source. The background of this study is based on the importance of a deeper understanding of the impact of teenage pregnancy on maternal mental health, given the high prevalence of teenage pregnancy in Indonesia and its long-term negative impact. The purpose of this study is to investigate the factors that support or hinder the mental health of mothers who experience teenage pregnancy, and to present key findings from the relevant literature in this context. The research method used was a qualitative analysis of relevant literature studies found through systematic searches in academic databases and scientific journals. This approach allowed us to explore the findings of various studies and gain an in-depth understanding of the phenomenon under study. The main results of this study show that teenage pregnancy has a significant impact on the mother's future mental health, including an increased risk of depression, anxiety and postnatal stress. Factors such as social support, access to mental health services, and economic conditions play an important role in determining the mother's future mental health. The conclusion of this study is that efforts to improve future maternal mental health should be a priority in public policy and clinical practice. A holistic approach that takes into account the various factors that influence maternal mental health, as well as cross-sectoral cooperation, is needed to create a supportive environment for adolescent mothers to achieve optimal mental well-being.